Model Kognitif Psikolinguistik Terkini dalam Menunjang Pembelajaran Struktur Bahasa Arab - Rizki Nugrahawan, Ahmad; Rafli, Zainal; Setiadi, Samsi (Tarling : Journal of Language Education, 2024)
Psycholinguistic understanding helps teachers to detail teaching strategiesthat take into account how students process Arabic information, understandsentence structure, and overcome potential learning difficulties. Cognitivetheory emphasizes aspects of understanding, mental processes, and organizationin language acquisition. This view states that the stages of students' cognitivedevelopment influence their language development. In this research, theeffectiveness of the cognitive model in learning Arabic becomes a benchmark indetermining whether the teacher's role is fulfilled in applying psycholinguistic teststo students. So that the latest alternative for learning Arabic has emerged basedon its new understanding. In this research, the researcher limited it to languagestructure material or often referred to as nahwu (syntax). Because learning nahwuholds great urgency in developing Arabic language skills. This research uses aqualitative descriptive approach, as well as the use of metasynthesis techniques forSLR (systematic literature review) research. With the systematic literature reviewmethod, research will be carried out using systematic, explicit and reproduciblesteps to synthesize (identify, evaluate, interpret) a number of research works andideas that have been produced by researchers. The results of this research, in thecognitive aspect, researchers found that structural learning of Arabic (Nahwu) withthe TBL (Task Based Learning) and PBL (Problem Based Learning) models is a learning model that can provide significant learning results in improving students' cognitive abilities, because both This model provides stimulus to students. Thus making cognitive abilities develop efficiently and effectively. This makes PBL andTBL alternative options in learning Arabic which is based on psycholinguisticcognitive models